Answer:
The equation seems to be something like:
-9 - 6*12h/40 = 22
but some of the signs are missing, i will try to give a some what general way of solivng these equations.
we want to solve it for h.
the first step is isolating h in one side of the equation, for this, we start adding 9 in both sides to remove the term that is not acting directly on h:
(-9 - 6*12h*40) + 9 = 22 + 9
- 6*12h*40 = 31
Now, we need to pass the terms that are acting directly on h, first we solve everithing we can:
-6*12*h/40 = -(6*12)*h/40 = -50/40*h = (-5/4)*h = 31
Now we divide in both sides by the number that is multiplicating h, so we can remove it:
(-5/4)/(-5/4)*h = h = 27/(-5/4) = (-27*4)/5 = -24.8
so for this particular equation, h = -24.8, but if the equation is different, you can do a similar proces to find the value og h.